A Comprehensive Systematic Review of Management of Otolaryngology Conditions in Low-Income Communities - Reza Gusni Saputra; Guntur Surya; Anggina Diksita Pamasya (International Medical Journal Corp. Ltd, 2025)
Introduction: Otolaryngology (ENT) care in low-income and resource-limited communities faces profound challenges due to systemic inequities, financial constraints, and limited access to specialists. Chronic suppurative otitis media (CSOM) and other ENT conditions disproportionately affect disadvantaged populations, leading to significant morbidity and preventable complications. Methods: This comprehensive systematic review synthesized evidence from 80 studies identified through rigorous screening. We included primary research and systematic reviews focusing on ENT condition management in low-income settings, low-resource environments, or among economically disadvantaged groups. Data extraction encompassed ENT conditions, population characteristics, management approaches, outcomes, barriers, facilitators, and resource requirements. Results: Chronic suppurative otitis media (CSOM) was the most frequently studied condition, with high prevalence linked to poverty, overcrowding, and poor hygiene (Minja et al., 2006; Clarke et al., 2015). Effective management strategies included community-based task-shifting, such as training community health workers (CHWs) in Malawi, which was both feasible and cost-effective at approximately 189 per CHW trained (Mulwafu et al., 2017). Telemedicine demonstrated high diagnostic concordance (>80%) and improved access (Ning et al., 2020; Dash et al., 2024). Low-cost pharmacological alternatives, like topical acetic acid and vinegar wash, showed comparable efficacy to more expensive antibiotics (Vishwakarma et al., 2015; Shenoy et al., 2017). Major barriers included financial limitations, geographic isolation, and systemic gaps in provider knowledge and resources (Beaudoin et al., 2020; Khoza-Shangase et al., 2020). Discussion: The evidence underscores the context-dependent success of interventions. Success hinged on community integration, the use of affordable and effective treatments, and technology-enhanced delivery models. Culturally appropriate, community-codesigned programs were essential for sustainability, particularly for Indigenous and marginalized populations (Gotis-graham et al., 2020). Conclusion: Prioritizing scalable, low-cost interventions—such as CHW training, telemedicine, and task-shifted care models—is crucial for improving ENT care equity in low-income communities. Future efforts must address long-term sustainability, contextual adaptation, and the integration of community-based and specialist services.